Kepuasan Pelanggan Terhadap Ketersediaan Layanan dan Fasilitas Pantai Setumu Tanjung Siambang Dompak - Afriyadi Afriyadi; Fitri Novira Viani; Mimi Syahfitri; Riska Saputri Wibowo; Tri Andini; Yuniati Nur Puspitasary; Zahrani Putri Tia Tara (Institut Nalanda, 2023)
Customer satisfaction with the availability of services and facilities is something that must be considered from a tourist spot, especially on beach tourism. Customer satisfaction is also a benchmark for customers to return to visit or use the products / services offered again. The purpose of this study is to find out related to customer satisfaction with the availability of services and facilities on the beach setumu tanjung siambang Dompak and is expected to be able to help beach owners in improving their services and facilities for customer satisfaction. This research uses qualitative methods through interviews with several visitors and direct observation of the field.